Reinterpretasi Hadis Ketaatan Istri Terhadap Suami Perspektif Qira’ah Mubadalah - Haitomi, Faisal (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2021)
AbstractThis article discusses about the relationship between husband and wife in the family which focuses on the hadith narrated by Ibn Majah through the Musawir al-Himyari route. This hadith is one of the many religious texts that are used to legitimize the marginalization of women, especially in the family realm. This research borrows the Mublah approach offered by Faqihuddin Abdul Kodir as an analytical tool that emphasizes cooperation and/or interdependence between two parties. From the discussion presented in this paper, the author comes to the conclusion that the hadith regarding the recommendation of a wife to seek and gain the pleasure of her husband, cannot be understood as one party only as emphasized by classical scholars. Partial texts like this when viewed from the point of view of mublah, are very contrary to the teachings of Islamic principles, especially in the family which emphasizes cooperation between husband and wife for the sake of creating a sakinah family, mawaddah warahmah. Therefore, it is not only the wife who is encouraged to seek and get the pleasure of her husband, but also vice versa in this case the husband also has the same obligations as those imposed on his wife.AbstrakArtikel ini membahas terkait relasi suami dan istri di dalam keluarga yang fokus  terhadap hadits riwayat Ibnu Majah melalui jalur Musawir al- Himyari. Hadits ini merupakan salah satu dari sekian banyak teks agama yang digunakan sebagai legitimasi atas pemarginalan perempuan, terlebih lagi dalam ranah keluarga. Riset ini meminjam pendekatan Mubadalah yang ditawarkan oleh Faqihuddin Abdul Kodir sebagai pisau analisis yang menekankan kerjasama dan atau ketersalingan antara dua belah pihak. Dari diskusi yang dihadirkan dalam paper ini, penulis sampai kepada kesimpulan bahwa hadits tentang anjuran istri mencari dan mendapatkan ridho suami, tidaklah bisa difahami sebagai salah satu pihak saja seperti yang ditegaskan oleh ulama klasik. Teks- teks parsial seperti ini jika dilihat dari sudut pandang mubadalah, sangatlah bertentangan dengan ajaran prinsip Islam terutama dalam keluarga yang menekankan kerjasama antara suami dan istri demi terciptanya keluarga sakinah, mawaddah warahmah. oleh karenanya tidak hanya istri yang dianjurkan mencari dan mendapatkan ridho suami, tetapi juga sebaliknya suami dalam hal ini juga memiliki kewajiban yang sama sebagaiamana yang dibebankan kepada istri.Kata Kunci: Hadits; Mubadalah; Relasi Suami Istri.